2021
DOI: 10.1111/jfpp.16011
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of various properties of a novel celery pulp powder manufactured using foam mat drying

Abstract: Celery (Apium graveolens), which is widely cultivated and consumed regularly all over the world, is a marshland plant in the family of Apiaceae with 114 genera and 420 species. This plant is of herbaceous and biennial nature, with an appearance of almost opaque green containing vertical roots (Sowbhagya, 2014). Different parts of the celery plant can be used in several food products such as beverages, soups, stews, salads, and pastas for different purposes; that is, as a flavoring ingredient, as well as an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Closer inspection of the results shows a direct relationship between the HG values and the moisture content of the powders, so that the material with the lowest moisture content (T = 60°C) was the one that most absorbed water during the experiment. The influence of temperature on hygroscopicity is in accord with the results obtained by Franco et al (2016) and by Bagheri et al (2021) on foam mat drying of yacon juice and celery pulp, respectively. According to the authors, the low hygroscopicity found at low temperatures can be explained by the fact that powders obtained under these conditions have higher moisture content and, consequently, lower moisture gradient between the product and the environment.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Closer inspection of the results shows a direct relationship between the HG values and the moisture content of the powders, so that the material with the lowest moisture content (T = 60°C) was the one that most absorbed water during the experiment. The influence of temperature on hygroscopicity is in accord with the results obtained by Franco et al (2016) and by Bagheri et al (2021) on foam mat drying of yacon juice and celery pulp, respectively. According to the authors, the low hygroscopicity found at low temperatures can be explained by the fact that powders obtained under these conditions have higher moisture content and, consequently, lower moisture gradient between the product and the environment.…”
Section: Resultssupporting
confidence: 91%
“…HG values obtained for the carrot top powders are shown in Figure 6a. In general, it is possible to note that these values – which ranged from 1.27 to 2.57%, are low when compared to those provided by Bagheri et al (2021) for the hygroscopicity of celery pulp powder (2.95–6.29%), and also by Shaari et al (2018) for pineapple powder (3.52–8.70%). This low hygroscopicity may be related to the addition of Emustab® in the foam preparation, since this additive is majority made by compounds with long nonpolar chains (fatty acid monoglycerides and sorbitan monostearate).…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…On the contrary, the highest emulsion activity, oil holding capacity, and foam holding stability and the lowest water holding capacity, emulsion stability, and foam holding capacity were observed at high‐drying temperature (70°C) in egg white foams (Çalışkan Koç & Çabuk, 2020). Considering the results of different literature studies, the increase in drying temperature caused a decrease in the solubility, lightness, protein content, and yield of the foam powders and an increase in the water solubility index, hygroscopicity, dispersibility, hue angle (−53.828 ± 3.194), L * (71.266 ± 0.665), and Δ E values (12.849 ± 1.779) (Bagheri et al, 2021; Gupta et al, 2021; Kamali et al, 2021; Wahyuni et al, 2021).…”
Section: Methodsmentioning
confidence: 99%